β2 Integrin-Mediated Susceptibility to Paracoccidioides brasiliensis Experimental Infection in Mice - de Oliveira, Stephan Alberto Machado; Reis, Janayna Nunes; Catão, Elisa; Amaral, Andre Correa; Souza, Ana Camila Oliveira; Ribeiro, Alice Melo; Faccioli, Lúcia Helena; Carneiro, Fabiana Pirani; Marina, Clara Luna Freitas; Bürgel, Pedro Henrique; Fernandes, Larissa; Tavares, Aldo Henrique; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
The earliest interaction between macrophages and Paracoccidioides brasiliensis is particularly important in paracoccidioidomycosis (PCM) progression, and surface proteins play a central role in this process. The present study investigated the contribution of β2 integrin in P. brasiliensis-macrophage interaction and PCM progression. We infected β2-low expression (CD18low) and wild type (WT) mice with P. brasiliensis 18. Disease progression was evaluated for fungal burden, lung granulomatous lesions, nitrate levels, and serum antibody production. Besides, the in vitro capacity of macrophages to internalize and kill fungal yeasts was investigated. Our results revealed that CD18low mice infected with Pb18 survived during the time analyzed; their lungs showed fewer granulomas, a lower fungal load, lower levels of nitrate, and production of high levels of IgG1 in comparison to WT animals. Our results revealed that in vitro macrophages from CD18low mice slowly internalized yeast cells, showing a lower fungal burden compared to WT cells. The migration capacity of macrophages was compromised and showed higher intensity in the lysosome signal when compared with WT mice. Our data suggest that β2 integrins play an important role in fungal survival inside macrophages, and once phagocytosed, the macrophage may serve as a protective environment for P. brasiliensis